Daily and intermittent smoking are associated with low prefrontal volume and low concentrations of prefrontal glutamate, creatine, myo‐inositol, and N‐acetylaspartate. (3rd December 2020) - Faulkner, Paul; Lucini Paioni, Susanna; Kozhuharova, Petya; Orlov, Natasza; Lythgoe, David J.; Daniju, Yusuf; Morgenroth, Elenor; Barker, Holly; Allen, Paul
Abstract: Cigarette smoking is still the largest contributor to disease and death worldwide. Successful cessation is hindered by decreases in prefrontal glutamate concentrations and gray matter volume due to daily smoking. Because nondaily, intermittent smoking also contributes greatly to disease and death, understanding whether infrequent tobacco use is associated with reductions in prefrontal glutamate concentrations and gray matter volume may aid public health. Eighty‐five young participants (41 nonsmokers, 24 intermittent smokers, 20 daily smokers, mean age 23 years old), underwent 1 H‐magnetic resonance spectroscopy of the medial prefrontal cortex, as well as structural magnetic resonance imaging (MRI) to determine whole‐brain gray matter volume. Compared with nonsmokers, both daily and intermittent smokers exhibited lower concentrations of glutamate, creatine, N ‐acetylaspartate, and myo‐inositol in the medial prefrontal cortex, and lower gray matter volume in the right inferior frontal gyrus; these measures of prefrontal metabolites and structure did not differ between daily and intermittent smokers. Finally, medial prefrontal metabolite concentrations and right inferior frontal gray matter volume were positively correlated, but these relationships were not influenced by smoking status. This study provides the first evidence that both daily and intermittent smoking are associated with low concentrations of glutamate, creatine, N ‐acetylaspartate, and myo‐inositol and low gray matter volume in the prefrontal cortex. Future tobacco cessation efforts should not ignore potential deleterious effects of intermittent smoking by considering only daily smokers. Finally, because low glutamate concentrations hinder cessation, treatments that can normalize tonic levels of prefrontal glutamate, such as N ‐acetylcysteine, may help intermittent and daily smokers to quit. Abstract : Intermittent smoking is associated with significant health risks. Although intermittent smokers struggle to quit, studies ignore this at‐risk population. We provide the first evidence that individuals who smoke approximately two cigarettes on a nondaily basis exhibit similarly low prefrontal glutamate, creatine, N‐acetylaspartate, myo‐inositol and gray matter volume as individuals who smoke at least half a pack of cigarettes every day. Because low levels of these metabolites can hinder smoking cessation, pharmacotherapies that increase such levels may help intermittent smokers to quit.